Nonhematopoietic Variants of Erythropoietin in Ischemic Stroke: Need for Step-Wise Proof-of-Concept Studies - Dirk M. Hermann (The Scientific World Journal)
Neuroprotective, but not hematopoietic, variants of erythropoietin (EPO), such as Neuro-EPO, are promising candidates for treatment in the acute and subacute stroke phase. Characterized by its low sialic acid content and therefore exhibiting a very short plasma half-life, Neuro-EPO can probably not be administered systemically via the blood. As such, alternate routes of delivery are required. In their paper that now appears in TheScientificWorldJOURNAL, Rodríguez Cruz and colleagues provide evidence that Neuro-EPO promotes neurological recovery in the ischemic gerbil brain in a way that is similarly potent, if not superior, to systemically administered EPO. In view of the potential clinical use of Neuro-EPO, stringent proof-of-concept studies are urgently needed to define (1) how intranasally delivered Neuro-EPO reaches the brain, (2) which concentrations are achieved in the ischemic and nonischemic brain tissue of rodents and nonhuman primates, and (3) which are the mechanisms via which Neuro-EPO protects from injury. Only with such information should decisions be made whether intranasal Neuro-EPO may be evaluated in human patients.